2020
DOI: 10.1093/jxb/eraa054
|View full text |Cite
|
Sign up to set email alerts
|

A balancing act: how plants integrate nitrogen and water signals

Abstract: Abstract Nitrogen (N) and water (W) are crucial inputs for plant survival as well as costly resources for agriculture. Given their importance, the molecular mechanisms that plants rely on to signal changes in either N or W status have been under intense scrutiny. However, how plants sense and respond to the combination of N and W signals at the molecular level has received scant attention. The purpose of this review is to shed light on what is currently known abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 103 publications
2
58
0
Order By: Relevance
“…In addition, it also showed that intercropping with soybean could change the relative abundance of the sugarcane rhizosphere bacterial community and form a different rhizosphere bacterial community structure from that of single cropping sugarcane (Paungfoo-Lonhienne et al, 2017 ). Since the phenotypic structure of the root system had an impact on water absorption, the available N was mostly soluble in water, so many root structural features that promote water absorption (such as root length and diameter) could also generally improve the absorption rate of N (Araus et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it also showed that intercropping with soybean could change the relative abundance of the sugarcane rhizosphere bacterial community and form a different rhizosphere bacterial community structure from that of single cropping sugarcane (Paungfoo-Lonhienne et al, 2017 ). Since the phenotypic structure of the root system had an impact on water absorption, the available N was mostly soluble in water, so many root structural features that promote water absorption (such as root length and diameter) could also generally improve the absorption rate of N (Araus et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These varieties have great advantages in yield and can replace the sugarcane varieties currently planted by farmers. Previous studies have found that ZZ1 and ZZ9 have differences in water-use efficiency, which also indicates differences in nitrogen use (Araus et al, 2020). Therefore, ZZ1 and ZZ9 may have different patterns when intercropped with soybean, and it is worth conducting an in-depth exploration of the intercropping benefits of these two varieties.…”
Section: Introductionmentioning
confidence: 98%
“…Low NO 3 − availability can also lower the transpiration rate (TR; Wilkinson et al, 2007) and consequently affect water use by crops. Araus et al (2020) showed that changes in NO 3 − availability may lead to changes in the expression of droughtresponse genes; this response also involves the drought stress hormone abscisic acid (ABA). An interesting detail is that nitrogen supply to roots enhances stomatal opening, provided that plants are well watered (Wilkinson et al, 2007;Matimati et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, asparagine synthase ( asn; Sobic.001G406800) was up-regulated across tissues, which would suggest increased N assimilation relative to uptake. The processes regulating water and N uptake and use must be tightly interconnected, yet currently largely not understood (Araus et al, 2020)…”
Section: Discussionmentioning
confidence: 99%